The Rice CK2 Kinase Regulates Trafficking of Phosphate Transporters in Response to Phosphate Levels. Issue 3 (27th February 2015) - Chen, Jieyu; Wang, Yifeng; Wang, Fei; Yang, Jian; Gao, Mingxing; Li, Changying; Liu, Yingyao; Liu, Yu; Yamaji, Naoki; Ma, Jian Feng; Paz-Ares, Javier; Nussaume, Laurent; et al.
Abstract : A kinase complex regulates phosphate transporter trafficking in response to phosphate, inhibiting interaction with the factor regulating exit from the endoplasmic reticulum to the plasma membrane. Abstract: Phosphate transporters (PTs ) mediate phosphorus uptake and are regulated at the transcriptional and posttranslational levels. In one key mechanism of posttranslational regulation, phosphorylation of PTs affects their trafficking from the endoplasmic reticulum (ER ) to the plasma membrane. However, the kinase(s) mediating PT phosphorylation and the mechanism leading to ER retention of phosphorylated PTs remain unclear. In this study, we identified a rice ( Oryza sativa ) kinase subunit, CK2β3, which interacts with PT2 and PT8 in a yeast two-hybrid screen. Also, the CK2α3/β3 holoenzyme phosphorylates PT8 under phosphate-sufficient conditions. This phosphorylation inhibited the interaction of PT8 with PHOSPHATE TRANSPORTER TRAFFIC FACILITATOR1, a key cofactor regulating the exit of PTs from the ER to the plasma membrane. Additionally, phosphorus starvation promoted CK2β3 degradation, relieving the negative regulation of PT phosphorus-insufficient conditions. In accordance, transgenic expression of a nonphosphorylatable version of OsPT8 resulted in elevated levels of that protein at the plasma membrane and enhanced phosphorus accumulation and plant growth under various phosphorus regimes. Taken together, these results indicate that CK2α3/β3 negatively regulates PTs and phosphorus status regulates CK2α3/β3.